2023
DOI: 10.5187/jast.2023.e19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different stocking density and various phytogenic feed additives dosage levels on growing-finishing pigs

Abstract: Competing interestsNo potential conflict of interest relevant to this article was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The growth performance was further reduced with increasing stocking density. Several studies demonstrated that limiting space allowance decreases feed intake and average daily gain in growing pigs even in optimum environment conditions [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth performance was further reduced with increasing stocking density. Several studies demonstrated that limiting space allowance decreases feed intake and average daily gain in growing pigs even in optimum environment conditions [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to suboptimal nutrition, the heat stress, the high stocking density, and the high NH3 induce inflammation, oxidative damage to cells, and reduce gut integrity, weakening the immune system of the animals making them more susceptible to infection and less efficient [49,[52][53][54]. NH3 irritates the conjunctiva causing conjunctivitis [55], irritates the mucosal layer of the respiratory system and depresses ciliary activity and mucus flow [56] and damaging trachea [57] which predisposing animals to infection.…”
Section: Discussionmentioning
confidence: 99%
“…PFAs are plant-derived bioactive compounds with elevated contents of flavonoids, tannins and mucilages with high antioxidant properties [22][23][24]. Additionally, supplementing fish diets with PFAS has been reported to be capable of attenuating different fish species' stress responses [25][26][27][28][29]. Plantderived prebiotic compounds are another variety of functional additives with a potential reinforcing fish antioxidant defense [22,29].…”
Section: Introductionmentioning
confidence: 99%